Profil Karakteristik Antropometri dan Kardiorespiratori Atlet Kota Serang - Rian Triprayogo; Danang Prama Dhani; Arief Nuryadin; Ida Zubaida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
In order to prepare athletes to take part in the Banten Regional Sports Week event, each athlete needs to know their fitness condition before undergoing training camp because physical condition can be used as a benchmark by the coach as a basis for determining the training program during the training camp. Therefore, this study aims to describe the profile of aerobic capacity and anthropometry in athletes in Serang City. This research will focus on sports that have many numbers to win medals, namely fencing, Pencak Silat, Futsal and Taekwondo. This type of quantitative descriptive research is used in this study by using a total sampling technique in sampling so as to produce a total of 60 athletes who come from the sports branches of Fencing, Pencak Silat, Taekwondo, and Futsal from Serang City. The results of this study indicate that the average aerobic capacity of male athletes in fencing, taekwondo, and pencak silat are 40.2 ml/kg/min, 34.1 ml/kg/min, 41.2 ml/kg/min, respectively. . Meanwhile, the aerobic capacity of female athletes in fencing, taekwondo, pencak silat, and futsal were 29.4 ml/kg/min, 34.5 ml/kg/min, 34.1 ml/kg/min, and 37, respectively. 4 ml/kg/min. Based on the results of the research and discussion in this study, the conclusions obtained are the average aerobic capacity of male fencing athletes, female pencak silat, female taekwondo, and female futsal athletes are in the less category. While the average aerobic capacity of female fencing athletes is in the very poor category. Keywords: Anthropometry, Cardiorespiratory, Athlete